Exome-wide analysis identify multiple variations in olfactory receptor genes (OR12D2 and OR5V1) associated with autism spectrum disorder in Saudi females - Almandil, Noor B.; Alismail, Maram Adnan; Alsuwat, Hind Saleh; AlSulaiman, Abdulla; AbdulAzeez, Sayed; Borgio, J. Francis (Frontiers in Medicine, 2023)
Background: Autism Spectrum Disorder (ASD) is a multifactorial, neurodevelopmental disorder, characterised by deficits in communication, restricted and repetitive behaviours. ASD is highly heritable in Saudi Arabia; indecencies of affected individuals are increasing. Objectives: To identify the most significant genes and SNPs associated with the increased risk of ASD in Saudi females to give an insight for early diagnosis. Methods: Pilot case-control study mostly emphasized on the significant SNPs and haplotypes contributing to Saudi females with ASD patients (n=22) compared to controls (n=51) without ASD. With the use of allelic association analysis tools, 243,345 SNPs were studied systematically and classified according to their significant association. The significant SNPs and their genes were selected for further investigation for mapping of ASD candidate causal variants and functional impact. Results: In females, five risk SNPs at p≤ 2.32×10-05 was identified in association with autism. The most significant exonic variants at chromosome 6p22.1 with olfactory receptor genes (OR12D2) and (OR5V1) clustered with high linkage disequilibrium through haplotyping analysis. Comparison between highly associated genes (56 genes) of male and female autistic patients with female autistic samples revealed that 39 genes are unique biomarkers for Saudi females with ASD. Conclusions: Multiple variations in olfactory receptor genes (OR5V1 and OR12D2) and single variations on SPHK1, PLCL2, AKAP9 and LOC107984893 genes are contributing to ASD in females of Arab origin. Accumulation of these multiple predisposed coding SNPs can increase the possibility of developing ASD in Saudi females.